PRELIMINARY PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF ETHANOLIC EXTRACT OF STEMS OF IPOMOEA AQUATICA FORSK. (FAMILY-CONVOLVULACEAE) - Chaudhury, Imdadul Haque; Das, Trishna; Saha, Dipankar (International Journal of Current Pharmaceutical Research, 2017)
Objective: To evaluate the antimicrobial activity ethanolic extracts of stems of the plant Ipomoea aquatica Forsk. (family-Convolvulaceae) along with preliminary phytochemical analysis. Methods: The ethanolic extract of stems of the plant Ipomoea aquatica Forsk. (family-Convolvulaceae) were prepared and analyzed for phytochemical constituents using standard methods. The antimicrobial activity of the plant extracts was examined against 2 bacterial strains among one is gram positive and other is gram negative and 2 fungus using agar well diffusion method. Results: The present experiment shows the phytochemical analysis, antimicrobial activity of the ethanolic extract of stems of the plant Ipomoea aquatic Forsk. (Family-Convolvulaceae). Various phytochemical analysis revealed the presence of alkaloids, saponin, flavonoids, carbohydrates, glycosides, Steroids, proteins and amino acids and tannins. All the extracts of the plant showed antimicrobial activity against most of the test organisms. Conclusion: The present study concluded that ethanolic extract of stems of the plant Ipomoea aquatica Forsk. Contain the high presence of phytochemical. The ethanolic extract of the plant was found to possess promising antimicrobial activity when compared with the standards. Â